Vale a pena elaborar uma unidade didática?!: percepções de alunos e de uma professora de inglês - Lopes, Valéria (2009)
This study aims at understanding if the teacher-researcher s participation in the preparation of the teaching unit in question could bring contributions to students learning at the same time disclosing possible reasons for those contributions. The importance of this research lies in the possibility to clearly comprehend the role of a teaching unit in the English teaching-learning process, from the teacher s and the students point of view. As theoretical bases, this investigation uses, among other concepts, the socio-historical-cultural view of teaching-learning (Vigotski, 1930/1998, 1934/2005), Parâmetros Curriculares Nacionais Língua Estrangeira (Brasil, 1998) and criteria for the production and evaluation of materials (Cunningsworth, 1984; Graves, 1996, 2000). Methodologically, it is a case study within the interpretive qualitative paradigm that for data collection makes use of questionnaires, reflective diaries, interviews and the final production of students resulting from the unit. The participants are the teacher-researcher and eight students from the 1st grade Ensino Médio , of a state school in the city of São Paulo. The results indicated that the teacher-researcher s participation in the preparation of the material brought contributions, as she felt better prepared to use the material in class and consequently the students learning was more adequately conducted